Volubilis après Rome : les fouilles UCL/INSAP, 2000-2005 - Fentress, Elizabeth; Līmān, Ḥassan (Arts and archaeology of the Islamic world, 2018)
The most-visited archaeological site in Morocco, Volubilis has long been known for its spectacular mosaics. Instead, this book deals with what happened to the town after the Roman administration was withdrawn at the end of the third century. The excavations published here show how the town continued to survive into the fifth century, with élite houses still commissioning elegant and witty mosaics, and how this occupation came to an end in a brutal earthquake. The town revived in the sixth century with new occupants, the Berber Awraba tribe. In the eighth century, it became the headquarters of the man who united most of Morocco at the head of the Awraba, Idris I, a descendant of the prophet Mohammed.